(untitled) (Impact: Journal of Transformation, 2022)
Work-related stress is of major concern due to its adverse impact on individuals, organisations and communities. Globalisation and constantly adapting to new technologies puts additional strain on workers to work faster and on tighter deadlines. The current study investigated the occurrence of work-related stress across a section of human resources directors, managers, assistant managers and supervisors in various organisations in Nairobi Metropolitan, Kenya. Human resources senior personnel were identified due to the critical role they play in wellness programmes in organisations. Nairobi Metropolitan was chosen due to the large number of organisations present. The study was an analytical cross-sectional study and the sampling technique was purposive. Data was collected from 201 participants from a population sample size of 271 indicating a response rate of 74%. Participants were invited via email invitation and on the social media platform LinkedIn. The Cohen Perceived Stress Scale (CPSS) was used to assess the prevalence of stress. Descriptive analysis was conducted to determine the occurrence of stress where 88.6% of respondents indicated elevated levels of stress. The study also found that 80% of respondents recorded moderate stress levels and 11% recorded low stress levels while only 9% of the respondents recorded high levels of stress. Since the research was undertaken during the COVID - 19 pandemic, it may have amplified the results of this research. Findings from the current study will benefit further research in this field and create additional awareness to organisations on this important issue.